An investigation of the roles of MYB transcription factors in orchid dendrobium hybrida flower development / Lau Su Ee - Lau, Su Ee (2013)
MYB genes encode a large family of transcription regulators in eukaryotes. Most plant MYB genes belong to the R2R3-MYB subfamily. MYB gene family members have been studied in various plant species and play roles in the regulation of plant development, hormone signalling, defence response and secondary metabolism. Orchid plants play an important role in the floral industry owing to their unique flower shapes, fragrance, colours and keeping quality. Flower colours are influenced by flower pigmentation, vacuolar compounds, pH, metal ions and shape of epidermal cells. R2R3-MYB genes regulate flower pigmentation, flower shape and cell shape therefore have importance in the development of new varieties of orchids. Polymerase chain reaction with sequence consensus based primer was used to amplify thirty-seven partial cDNA fragments representing R2R3-MYB gene sequences were isolated from Dendrobium hybrida. Phylogenetic analysis with IT3F: An Interspecies Transcription Factor Function Finder for Plants (http://jicbio.bbsrc.ac.uk/IT3F) of the translated R2R3-MYB gene sequences revealed that MYB sequences from Dendrobium hybrida are clustered into six subgroups. Nine of the translated DhMYB genes were clustered in subgroup 9 which are known to be involved in cell shape development. Production of dsRNA, sense and antisense RNAs were synthesized in vitro from the corresponding DNA plasmids by using double T7 RNA polymerase. RNAi knock down of the expression of DhMYB using dsRNA approach showed significant reduction of DhMYB gene expression compared with untreated control. Cell shape scanning electron microscopy of adaxial epidermal cells within domain 1 of the lip of flowers treated with DhMYB dsRNA had flattened epidermal cells whilst those of control flowers were conical – papillate. We suggest that DhMYB cDNA controls cell morphogenesis in the lip epidermis.